THE PROBLEM DOWN PAYMENT (DP) IN ONLINE BUYING AND SELLING AGREEMENT - Rizka, Fathia Tari; Dajaan, Susilowati S. (Program Studi Magister Hukum Universitas Malikussaleh, 2024)
The growing fast of convenience in electronic transactions or known as E-commerce, followed by many people in Indonesia becoming more consumptive in shopping online. However, behind all the convenience and benefits obtained, there is another concern that the rise of online sellers who are not responsible for e-commerce consumers. To respect the rights of consumers, complete, accurate information, as well as regulatory regulations on the security of the online buying and selling system in this case using a down payment (DP) system is very important for the purchase of an item in upholding consumer rights. The writing method of this research uses normative juridical research and uses a statutory approach, namely Undang-undang No. 8 Tahun 1999 Tentang Perlindungan Konsumen dan Undang-Undang No. 11 Tahun 2008 sebagaimana telah diubah dengan Undang-Undang No 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik, which focuses on consumer rights and business liability in the form of business liability for losses by consumers.